Hypoalbuminemia as a predicator of mortality of sepsis from COVID-19. Hospital II Chocope, 2020.: Hipoalbuminemia como predictor de mortalidad de sepsis por COVID-19. Hospital II Chocope, 2020. - Lopez, Alex Brandon (2020)
A correlational type investigation was carried out evaluating 145 patients with covid-19 sepsis. Objectives: To determine whether hypoalbuminemia is a predictor of mortality and to identify the serum albumin value most frequently related to lethality. Method: Patients older than or equal to 18 years seen at Hospital II Chocope during May to August 2020 were included. Patients with oncological pathologies and incomplete medical records were excluded. The documentary analysis technique was used, by reviewing medical records. Results: There was a statistically significant association between hypoalbuminemia and mortality (p = 0.00), patients with hypoalbuminemia had 3 times the risk of dying. (OR = 3.97 95% CI). Likewise, the highest sensitivity and specificity of the test was when the cut-off point for hypoalbuminemia was 1.38 g / dl. Finally, the most frequent comorbidity was arterial hypertension. Conclusions: hypoalbuminemia is a predictor of mortality and the lower the albumin value, the higher the mortality.